Chemical management of weeds in wheat culture - Galon, Leandro; Oliveira, Barbara Casagrande de; Bagnara, Maico André Michelon; Schmitz, Moises Henrique; Oliveira, Camila Viasdeski de; Pigatto, Sabrina Camila; Mezadri, David Fambre; Tironi, Siumar Pedro (Brazilian Journal of Science, 2023)
Weeds compete with wheat for water, light, and nutrients, which reduces productivity and thus profits for the wheat producer. Therefore, the objective of this work was to evaluate the selectivity and efficacy of herbicides applied pre-emergence and post-emergence to control weed-infesting wheat. Two experiments were set up in randomized blocks, with four replicates. Pre-emergence herbicides used were imazethapyr + flumioxazin, pendimethalin, and flumioxazin; post-emergence herbicides used were iodosulfuron, pyroxsulam, metsulfuron, and clodinafop, and two controls, one weeded and the other infested. The herbicides with the highest phytotoxicity for the wheat cultivar TBIO Sinuelo were the mixture of imazethapyr + flumioxazin and associated with this the use of iodosulfuron, pyroxsulam, metsulfuron, and clodinafop. The application of imazethapyr + flumioxazin + metsulfuron resulted in the least damage to wheat physiological variables. Pre-emergence use of imazethapyr + flumioxazin and the post-emergence use of iodosulfuron, pyroxsulam, and metsulfuron resulted in the best turnip control. The best ryegrass control was achieved by using pendimenthalin and flumioxazin in conjunction with clodinafop. The treatments imazethapyr + flumioxazin, imazethapyr + flumioxazin + iodosulfuron, pendimenthalin + iodosulfuron, flumioxazin + iodosulfuron, imazethapyr + flumioxazin + pyroxsulam, pendimenthalin + pyroxsulam, flumioxazin + pyroxsulam, imazethapyr + flumioxazin + clodinafop and flumioxazin + clodinafop were the most effective treatments for black oat control. The pendimenthalin + iodosulfuron showed the best responses in both experiments, both in terms of selectivity and efficacy, for grain yield components